Research on Urban Rail Traffic Load Modelling Method Based on Multi-Objective Function Optimization - Gu, Chengyu; Zheng, Xin; Chen, Hongtao; Li, Ju; Tong, Xianliang; Tan, Naijiu (2023 3rd International Conference on New Energy and Power Engineering (ICNEPE), 2023)
Due to the spatiotemporal and spatial differences in subway load, there is a load imbalance phenomenon on the main transformer load and power supply lines, which reduces the reliability of the power supply network. By analyzing the structure of the subway power supply network, this article establishes a traction station load model based on train schedules, and operates switches according to different objective functions to reduce peak load and achieve energy-saving effects